WEB PREDICATED INTERACTIVE ADVERTISEMENT AGENCY - Lency Preethi S.; Kaviya Priya S.; Judith Acquline M. (Galaxy International Interdisciplinary Research Journal, 2022)
The design entitled “ WEB predicated INTERACTIV ADVERTISING AGENCY ”. The main end of this design is to give advertisement details like advertisement cost in various channels. Depending upon the budget the various channels can lot different adverts also the total anterior end developed usingAsp.Net and backend is developed using SQL garçon. If an agency does not communicate or bear its client’s pretensions and creative wishes properly problems can do. utmost Full- Service Agencies work on a combination of figure- predicated and commission- predicated compensation.